Two parallel chromosome‐level reference genomes to support restoration and aquaculture of European flat oyster Ostrea edulis. (16th August 2022) - Bean, Tim P.; Tanguy, Arnaud; Peñaloza, Carolina; Gundappa, Manu Kumar; Boutet, Isabelle; Houston, Ross D.; Macqueen, Daniel J.; Boudry, Pierre
Abstract: This volume of Evolutionary Applications sees the publication of two genomes for the European native flat oyster Ostrea edulis, a species of significant evolutionary, ecological and commercial value. Each is a highly contiguous chromosome‐level assembly from individuals of different genetic backgrounds, which have been benchmarked against one another. This situation has resulted from the serendipitous discovery that two independent research groups were both deep into the process of building, annotating and investigating separately produced assemblies. Due to constraints with funder requirements and the need to recognize early career researchers for their work, alongside the technical challenge of integrating assemblies from two very different genomes, there was limited capacity to merge the sequences into one publication at the stage of discovery. This issue is likely to become very common over the next few years until the technologies for working with multiple genomes at once, for example, graph genomes, become commonplace in nonmodel species. Consequently, both of our teams have decided to collaborate rather than compete, recognizing the benefit to copublishing two separate genome resources for the research community, each with distinct scientific investigations, and working collaboratively to benchmark the assemblies.